2021
DOI: 10.1097/jom.0000000000002191
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Metabolic and Cardiovascular Risk Factors During Critical Training in Wildland Firefighters

Abstract: Objective:To identify physiologic stressors related to cardiovascular disease via changes in metabolic, inflammatory, and oxidative stress biomarkers during 2 weeks of preseason training in wildland firefighters (WLFFs).Methods:Participants were recruited from a local hotshot crew and monitored during preseason training. Fitness was assessed via the Bureau of Land Management fitness challenge. Venipuncture blood was collected on days 1, 4, 8, and 11 and analyzed for changes in a lipid and glucose panel, C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Notably, these alterations are despite normal pretraining levels of these markers in an already fit population. These results are similar to those of a previous report from our laboratory 18 but expand the generalizability since each IHC undergoes a unique training stimulus. This study also demonstrated a significant PV expansion over the course of 2 wk.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, these alterations are despite normal pretraining levels of these markers in an already fit population. These results are similar to those of a previous report from our laboratory 18 but expand the generalizability since each IHC undergoes a unique training stimulus. This study also demonstrated a significant PV expansion over the course of 2 wk.…”
Section: Discussionsupporting
confidence: 90%
“…However, pre-season critical training typically occurs before WLFFs begin fire assignments, meaning the potential influence of chronic exposure to the stressors of sleep disturbance and wood smoke are not present. 33,34 Support for these acute benefits in cardiovascular risk profiles can be gleaned from fundamentally similar investigations of Alaskan backcountry hunting expeditions. For example, examinations of risk profiles in hunters completing such expeditions up to 12 days revealed similar rapid improvements in total cholesterol (À44 mg dL À1 ), LDL-cholesterol (À25 mg dL À1 ), VLDL-cholesterol (À7 mg dL À1 ), triglycerides (À35 mgdL À1 ), triglyceride:HDLcholesterol ratio (À0.5), intrahepatic lipids (À0.3% water peak), body mass (À1.5 kg), and total fat mass (À1.7 kg).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies examining WLFFs during an 80-hour (over ∼ 11 days) “critical training” (conditioning) period prior to the fire season indicate transient improvements in total cholesterol (−11%), 33 LDL-cholesterol (−18%), 33 body fat percentage (−2% to −1%), 33 34 and lean body mass (+1 kg), 34 resulting in a more favorable cardiovascular risk profile. However, pre-season critical training typically occurs before WLFFs begin fire assignments, meaning the potential influence of chronic exposure to the stressors of sleep disturbance and wood smoke are not present 33,34 . Support for these acute benefits in cardiovascular risk profiles can be gleaned from fundamentally similar investigations of Alaskan backcountry hunting expeditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations